2017
DOI: 10.1016/j.neuroscience.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Touchscreen learning deficits and normal social approach behavior in the Shank3B model of Phelan–McDermid Syndrome and autism

Abstract: SHANK3 is a synaptic scaffolding protein localized in the postsynaptic density and has a crucial role in synaptogenesis and neural physiology. Deletions and point mutations in SHANK3 cause Phelan–McDermid Syndrome (PMS), and have also been implicated in autism spectrum disorder (ASD) and intellectual disabilities, leading to the hypothesis that reduced SHANK3 expression impairs basic brain functions that are important for social communication and cognition. Several mouse models of Shank3 deletions have been ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 70 publications
1
65
0
Order By: Relevance
“…Touch-screen automated paradigms have become increasingly utilized to screen rodent models of numerous neuropsychiatric disorders (Marquardt et al, 2014, Yang et al, 2015, Copping et al, 2016, Leach et al, 2016) as these paradigms closely model tools used in the clinical assessment and may increase translational potential of preclinical studies (Mar et al, 2013, Talpos and Steckler, 2013, Hvoslef-Eide et al, 2016). While previous studies have demonstrated that lesion and/or inactivation of the region is sufficient to disrupt visual touch-screen reversal, it has not yet been demonstrated that the rodent OFC mediates reversal of complex visual stimuli in an analogous manner to those seen in primates using visual stimuli (Clarke et al, 2008), or to more species-specific stimuli such as spatial, olfactory or tactile stimuli in rodents (Hamilton and Brigman, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Touch-screen automated paradigms have become increasingly utilized to screen rodent models of numerous neuropsychiatric disorders (Marquardt et al, 2014, Yang et al, 2015, Copping et al, 2016, Leach et al, 2016) as these paradigms closely model tools used in the clinical assessment and may increase translational potential of preclinical studies (Mar et al, 2013, Talpos and Steckler, 2013, Hvoslef-Eide et al, 2016). While previous studies have demonstrated that lesion and/or inactivation of the region is sufficient to disrupt visual touch-screen reversal, it has not yet been demonstrated that the rodent OFC mediates reversal of complex visual stimuli in an analogous manner to those seen in primates using visual stimuli (Clarke et al, 2008), or to more species-specific stimuli such as spatial, olfactory or tactile stimuli in rodents (Hamilton and Brigman, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…There were also no differences found on reversal learning (Peça et al, 2011). However, another study showed Shank3 B HTs were slower to reach criterion on a more difficult pairwise visual discrimination task (Copping et al, 2017). Here, subjects were tested on a complex 4/8 radial arm water maze and Shank3B KOs displayed robust deficits in reference memory.…”
Section: Discussionmentioning
confidence: 99%
“…Cohort 1 were offspring of Shank3 1/2 3 Shank3 1/2 breeding pairs, sampled from 9 litters, and tested in open field locomotion at PND 38-40 to confirm typical motor abilities. Pronounced locomotor deficits have been reported in Shank3 mouse models [Peca et al, 2011;Kouser et al, 2013;Speed et al, 2015;Jaramillo et al, 2016;Mei et al, 2016;Copping et al, 2017a;Dhamne et al, 2017] and thus it was crucial that the social communication outcomes of this study not be confounded by motor deficiencies. Cohort 2 were offspring of Shank3 1/2 3 Shank3 1/2 breeding pairs, sampled from 16 litters, and tested in acoustic playback of prosocial species-specific 50-kHz USV at PND 26-33.…”
Section: Behavioral Assaysmentioning
confidence: 98%